Crude glycerol esterification using biomass-derived carbon acid catalysts - Perez, Federico Martín (2024)
In this work, carbons obtained from peanut shells (PC), activated with KOH (APC) and functionalized with H2SO4 (PC-F and APC-F, respectively) were evaluated as catalysts in the esterification of crude glycerol with acetic acid to obtain monoacetyl glycerol, diacetyl and triacetyl glycerol. The characterization revealed that both PC-F and APC-F have high specific surface areas and very strong acid sites due to the presence of -HSO3 groups. The activity of both catalysts was evaluated using crude glycerol obtained from biodiesel synthesis, which presented acid pH, water, methanol, Na2SO4 and non-glycerol organic matter (MONG) as major impurities. The APC-F catalyst was more active than PC-F due to the combination of its surface acidity and textural properties. After 5 reaction cycles at 120 ◦C, using an acetic acid/glycerol molar ratio of 6 and a catalyst/glycerol mass ratio of 0.25, APC-F showed a decrease in specific surface area and pore volume due to the adsorption of Na2SO4 present in the crude glycerol. However, it was able to maintain activity levels with 100% glycerol conversion and selectivity to monoacetyl glycerol, diacetyl glycerol and triacetyl glycerol of 55%, 35% and 10%, respectively.